Evaluation of ethnobotanical knowledge in Komkar-Adi Biocultural Landscape of Eastern Himalayan Region of India (Asian Journal of Ethnobiology, 2020)
Abstract. Taram M, Borah D, Mipun P, Taram V, Das A.P. 2020. Evaluation of ethnobotanical knowledge in Komkar-Adi Biocultural Landscape of Eastern Himalayan Region of India. Biodiversitas 3: 70-87. The present study was aimed to document the traditional ethnobotanical knowledge in Komkar-Adi Biocultural Landscape of Upper Siang District in Arunachal Pradesh (Eastern Himalaya), India. Data was collected from three villages of Geku circle, Upper Siang District, between 2016-2019, covering more than 50% of the households using semi-structured questionnaires, personal interviews, focused group discussions, and transect walk with the core respondents. A total of 301 taxa falling in 203 genera and 85 families are recorded from the Komkar-Adi Biocultural Landscape (KABL), invariably used as food, medicine, and cultural material are directly and indirectly linked with livelihood security, community survival, protection, and preservation of the traditional culture and nature. Use value (UV) of all the reported species ranges between 0.017 and 0.051. 48 ethnomedicinal plant species were recorded, including herbs, shrubs, and trees, to cure 35 different ailments. Comparison of three other indices CI, RFC, and RI, indicating species ranking based on each index and the three fundamental values of the study, viz. FC, UR, and NU for each species were also calculated. Urtica dioica, Solanum spirale, Paris polyphylla, Curcuma longa, Clerodendrum colebrookeanum, and Begonia silletensis are essential for treating different ailments by the community.
Keywords: Conservation ethics, ethnobotany, Komkar-Adi, quantitative approach, traditional knowledge